The Effect Of Cash Flow, Profitability, And Leverage On Financial Distress In Listed Consumption Goods Companies - Silvia Oktari; Mohammad Fany Alfarisi; Rida Rahim (Jurnal Impresi Indonesia, 2023)
Introduction: Financial distress is a condition where a company experiences problems with its finances so that the company is threatened with bankruptcy. Purpose: This study aims to determine and analyze the effect of cash flow, profitability, and leverage variables partially on financial distress, as well as to determine which variable has the most dominant effect on financial distress in manufacturing companies in the consumer goods sector. The data processed is secondary data from the annual reports of 46 manufacturing companies in the consumer goods sector listed on the IDX for 2018-2021 taken through purposive sampling. The method used in this study is panel data regression analysis using Eviews version 10. The results of this study indicate that: cash flow has a significant positive effect on financial distress, profitability has a significant negative effect on financial distress, and leverage has a significant positive effect on financial distress. Methods: This study used a purposive sampling technique with a sample of 46 manufacturing companies in the consumer goods sector. Results: This study found that cash flow had a significant positive effect on financial distress, profitability had a significant negative effect on financial distress, and leverage had a significant positive effect on financial distress. Conclusion: It can be concluded that in this study cash flow and profitability have no significant effect on financial distress while leverage has a negative and significant effect on financial distress in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021